Letters to a fiction writer - 4 0 16; 1941- Busch, Frederick; 5 (New York : Norton, 1999)
Presents a collection of letters written by established authors to aspiring fiction writers.
Library Journal;Booklist;Reference and Research Book News
Adult;Adult
Keywords: 2 -- 0; 6; Authorship.;Authorship. -- Fiction;Authors, American;Fiction;American authors -- 20th century -- Correspondence.;Correspondence.; 20; 2